Sugammadex for reversal of neuromuscular blockade in a patient with myasthenia gravis: A comprehensive case report - Lohanathan, Aparna; Chelliah, Subbiah; Varadarajan, Ramesh (Indian Journal of Case Reports, 2025)
Myasthenia gravis (MG) is an autoimmune neuromuscular disorder characterized by muscle weakness. Surgical management of myasthenic patients requires careful perioperative planning to minimize the risks associated with anesthesia and surgery. Neuromuscular blocking agents (NMBAs) predispose such patients to post-operative residual paralysis and respiratory complications. One critical aspect is the reversal of neuromuscular blockade. Sugammadex, a modified γ-cyclodextrin, reverses the effects of steroidal NMBAs and is not accompanied by the risk of triggering a cholinergic crisis, a potential complication with cholinesterase inhibitors. We report the perioperative management of a 56-year-old female with MG undergoing thymectomy.